A study of current design & build procurement approach practice based on the client‟s specific expectations in the Malaysian Construction Industry - Gambo, Muhammad Mustapha (2011)
Design and build procurement approach is being considered as one of the innovative procurement approaches that is widely gaining popularity globally. The Malaysian construction industry is not left out in the growing adoption of this procurement approach, this could be attributed to the several advantages that the system offers to construction clients which includes single point responsibility, fixed cost, shortened project duration and risk allocation. However, with all these inherent advantages of the procurement approach, it is yet to be effectively adopted and practiced in the Malaysian construction industry. This study is aimed at appraising the Design &Build (D&B) procurement approach in the Malaysian Construction Industry based on current practice through identifying the impeding and enabling factors to the achievement of the client‟s specific expectations in order to enable the better practice of D&B procurement approach in the industry. Data was collected from a two round Delphi questionnaire survey which was conducted in Malaysia in order to identify the features that characterize the D&B procurement approach, and also the impeding and enabling factors in the achievement of the client‟s specific expectations. The key findings in the study showed that the practice of the system in Malaysia is most importantly characterized by the fact that the system is most suitable for projects that are complex in nature. Whilst the impeding and enabling factors in the achievement of the client‟s specific expectations which are attributed to be client related, contractor related and also external environment related was determined. It is expected that with the consideration of these impeding and enabling factors to the achievement of the client specific expectations, it will consequently result in the enhanced D&B project delivery, the better practice of the procurement approach; and ultimately the overall improvement of the performance of the Malaysian construction industry in relation to D&B projects.